Risk of adverse neonatal outcomes among pregnant women with disabilities. (28th September 2022) - Gleason, Jessica L; Grewal, Jagteshwar; Chen, Zhen; Cernich, Alison N; Grantz, Katherine L
Abstract: Background: To compare risk of neonatal morbidities between women with and without documented disability and to evaluate mediation of these associations by pre-term birth and caesarean delivery. Methods: Using data from the Consortium on Safe Labor (2002–2008; n  = 223 385), we evaluated risk of 22 neonatal outcomes among singleton deliveries using ICD-9 codes to define physical ( n  = 1733), sensory ( n  = 250) and intellectual disability ( n  = 91). Adjusted relative risk (aRR) was estimated for each outcome among each category of disability, and among women with any disability using Poisson regression models with robust variance. Causal mediation methods evaluated pre-term birth and caesarean delivery as mediators. Results: Compared with no disability, neonates of women with any disability had higher risk of nearly all neonatal outcomes, including pre-term birth (aRR = 1.77; 95% CI 1.62–1.94), small for gestational age (SGA) (aRR = 1.25; CI 1.11–1.41), neonatal intensive care unit (NICU) admission (aRR = 1.70; CI 1.54–1.87), seizures (aRR = 2.81; CI 1.54–5.14), cardiomyopathy (aRR = 4.92; CI 1.15–20.95), respiratory morbidities (aRR ranged from 1.33–2.08) and death (aRR = 2.31; CI 1.38–3.87). Women with disabilities were more likely to have a maternal indication for pre-term delivery, including pre-pregnancy diabetes (aRR = 3.80; CI 2.84–5.08), chronic hypertension (aRR = 1.46; CI 0.95–2.25) and severe pre-eclampsia/eclampsia (aRR = 1.47; CI 1.19–1.81). Increased risk varied but was generally consistent across all disability categories. Most outcomes were partially mediated by pre-term birth, except SGA, and heightened risk remained for NICU admissions, respiratory distress syndrome, anaemia and a composite of any adverse outcome (aRR = 1.21; CI 1.10–1.32). Conclusion: Neonates of women with disabilities were at higher risk of a broad range of adverse neonatal outcomes, including death. Risks were not fully explained by pre-term birth.